Affordance embeddings for situated language understanding - Krishnaswamy, Nikhil; Pustejovsky, James (Frontiers in Artificial Intelligence, 2022)
Much progress in AI over the last decade has been driven by advances in natural language processing technology, in turn facilitated by large datasets and increased computation power used to train large neural language models. These systems demonstrate apparently sophisticated linguistic understanding or generation capabilities, but often fail to transfer their skills to situations they have not encountered before. We argue that computational situated grounding of linguistic information to real or simulated scenarios provide a solution to some of these learning challenges by creating situational representations that both serve as a formal model of the salient phenomena, and contain rich amounts of exploitable, task-appropriate data for training new, flexible computational models. We approach this problem from a neurosymbolic perspective, using multimodal contextual modeling of interactive situations, events, and object properties, particularly afforded behaviors, and habitats, the situations that condition them. These properties are tightly coupled to processes of situated grounding, and herein we discuss we combine neural and symbolic methods with multimodal simulations to create a platform, VoxWorld, for modeling communication in context, and we demonstrate how neural embedding vectors of symbolically-encoded object affordances facilitate transferring knowledge of objects and situations to novel entities, and learning how to recognize and generate linguistic and gestural denotations.